A novel Immuno-Polymerase chain reaction protocol incorporating a highly purified Streptavidin-DNA conjugate - Shan, J.; Toye, Philip G. (Informa UK Limited, 2009)
We have developed an immuno-polymerase chain reaction protocol which includes a highly purified streptavidin-DNA conjugate. The protocol comprises standard ELISA methodology and washing buffers together with a real-time PCR read-out system. The conjugate was employed in both indirect and capture assay formats, which can be completed in a single day using standard laboratory equipment. The immuno-PCR is reproducible, with a larger dynamic range and a sensitivity several orders of magnitude greater than the corresponding conventional ELISA. The minimum concentration of analyte detected was of the order of 1 pg/mL These characteristics should contribute to the adoption of immuno-PCR by research and clinical laboratories.